2022
DOI: 10.3389/fonc.2022.834307
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Biological Function of Galectins in Malignant Glioma

Abstract: Malignant glioma is the most common solid tumor of the adult brain, with high lethality and poor prognosis. Hence, identifying novel and reliable biomarkers can be advantageous for diagnosing and treating glioma. Several galectins encoded by LGALS genes have recently been reported to participate in the development and progression of various tumors; however, their detailed role in glioma progression remains unclear. Herein, we analyzed the expression and survival curves of all LGALS across 2,217 patients with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…We demonstrated that LGALS1 is involved in immunosuppression, might be correlated with reduced survival in GBM patients, and that LGALS1 KO in GBM tumor cells can transform the immune landscape. Several research groups have reported similar findings (Baker et al, 2014;Barnes et al, 2018;Chou et al, 2018;Chen et al, 2019;Sharanek et al, 2021;Guda et al, 2022;Zhu et al, 2022). LGALS1 has been shown to drive resistance to chemo-and immunotherapy, and to be associated with poor survival.…”
Section: Discussionmentioning
confidence: 61%
“…We demonstrated that LGALS1 is involved in immunosuppression, might be correlated with reduced survival in GBM patients, and that LGALS1 KO in GBM tumor cells can transform the immune landscape. Several research groups have reported similar findings (Baker et al, 2014;Barnes et al, 2018;Chou et al, 2018;Chen et al, 2019;Sharanek et al, 2021;Guda et al, 2022;Zhu et al, 2022). LGALS1 has been shown to drive resistance to chemo-and immunotherapy, and to be associated with poor survival.…”
Section: Discussionmentioning
confidence: 61%
“…Intriguingly, Gal-8 is expressed only in tumor prostate cells other than normal prostate tissue, implying its potential as a specific biomarker for prostate cancer [ 54 ]. Gal-8 has also been reported to involved in tumor cell proliferation, adhesion, migration and EMT in lung cancer, breast cancer, ovarian cancer, and malignant glioma [ 17 , 38 , 55 57 ]. Mechanically, Gal-8 regulates the adhesion and migration of lung cancer cells by binding to integrins and activates the downstream focal adhesion kinase (FAK) pathway [ 56 ], promoting breast cancer cell migration through interacting with activated leukocyte cell adhesion molecule such as CD166/ALCAM receptors [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer and malignant melanoma, overexpression of cytoplasmic Gal-9 may inhibit tumor metastasis and attenuate recurrence [ 65 ]. More recently, Gal-9 indicates emerging potential as a therapeutic target for cancers, by serving as a good prognostic factor for kidney cancer and an independent indicator of poor prognosis in glioma [ 38 , 66 ]. Gal-9 also possesses immunomodulatory effects by serving as a ligand for T-cell immunoglobulin and mucin structural domain protein 3 (Tim-3), which are crucial for anticancer immunity [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite various therapies have emerged for GC patients, most of the patients' treatment still fail finally, which is due to drug resistance, tumor recurrence, and metastasis. 1 Cancer stem cells (CSCs) or cancer stemness has been considered to be one of the root of drug resistance, tumor metastasis, and occurrence. 2 Therefore, it is urgent to find new potential targets to deal with GC stemness.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) holds its high fatality rate and morbidity around the world. Despite various therapies have emerged for GC patients, most of the patients' treatment still fail finally, which is due to drug resistance, tumor recurrence, and metastasis 1 . Cancer stem cells (CSCs) or cancer stemness has been considered to be one of the root of drug resistance, tumor metastasis, and occurrence 2 .…”
Section: Introductionmentioning
confidence: 99%